Advokat dan Pemberantasan Korupsi - Erman Radjagukguk (Fakultas Hukum Universitas Islam Indonesia, 2008)
The role of advocates is of significant importance in the corruption eradication, especially in the side of litigation process. During litigation process, there is ethical dilemma experienced by such advocates in accomplishing advocacy on behalf of the client. In such situation, the courage of an advocate in holding up the Advocate Ethical Codes is very demanding.